1996
DOI: 10.1302/0301-620x.78b6.0780930
|View full text |Cite
|
Sign up to set email alerts
|

The Orthopaedic Implications of Peripheral Limb Ischaemia in Infants and Children

Abstract: P eripheral limb ischaemia is rare in children. We have treated only 12 infants and children with this condition in the past 15 years at the Royal Hospital for Sick Children in Glasgow. There were nine neonates and three older children. Most were suffering from life-threatening illnesses or severe infection. Two were born with ischaemic arms with no apparent cause. We have analysed the factors leading to ischaemia, the outcome of the initial treatment and the later orthopaedic problems. Two required amputation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It seems that, in children who survive the initial resuscitation, there is seldom the need to perform upper limb or above-knee amputations. While this study supports this hypothesis, some authors have described forearm amputation [4,13] or above-knee amputation [14].…”
Section: Discussionsupporting
confidence: 79%
“…It seems that, in children who survive the initial resuscitation, there is seldom the need to perform upper limb or above-knee amputations. While this study supports this hypothesis, some authors have described forearm amputation [4,13] or above-knee amputation [14].…”
Section: Discussionsupporting
confidence: 79%
“…A study from the Royal Hospital of Sick Children in Glasgow identified 12 children treated by the orthopedic department between 1977 and 1992 for limb ischemia with or without gangrene. 2 In that series, nine were neonates. All 12 cases were treated conservatively, and no surgery was undertaken until a line of demarcation had been well established.…”
Section: Discussionmentioning
confidence: 90%
“…This algorithm includes invasive options but as the review by Farrar et al showed, the results following conservative management are devastating. 2 Because of the continued improvement in microsurgical techniques, we believe that surgical treatment options should be considered in the neonate and that the sizes of the vessels are no longer a contraindication.…”
Section: Angiogrammentioning
confidence: 99%
“…Secondary operations of the amputation stumps, grafts, and scar correction may be necessary [21]. In cases of asymmetric bone growth resections must be done [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, below this age the risk of PF is greatest. The clinical picture and dramatic evolution of some of these cases are described in publications of a large variety of medical specialities [1,2,4,7,8,9,24]. Bacteria are most frequently involved (Neisseria meningitidis, Haemophilus influenzae, Streptococcus b-haemolyticus, Pseudomonas aeruginosa), as are viruses (Varicella zoster).…”
Section: Introductionmentioning
confidence: 99%